Terpene−Shikimate conjugated meroterpenoids from the endophytic fungus Guignardia mangiferae. (October 2021) - Chen, Keliang; Chen, Chunmei; Liu, Xiulan; Sun, Weiguang; Deng, Yanfang; Liu, Junjun; Wang, Jianping; Luo, Zengwei; Zhu, Hucheng; Zhang, Yonghui
Abstract: Nine undescribed shikimate-conjugated meroterpenes, as well as nine known compounds, were isolated from solid cultures of the fungus Guignardia mangiferae, an endophyte obtained from the leaves of Dendrobium nobile . The structures of these undescribed compounds were characterized by analyses of their 1D and 2D NMR and HRESIMS data, and their absolute configurations were assigned by single-crystal X-ray crystallography, electronic circular dichroism (ECD) calculations, modified Mosher's method, and Mo2 (OCOCH3 )4 -induced ECD experiments. Of these compounds, mangnardone A represents the first example of terpene–shikimate-conjugated meroterpenoid with a hydroxy group at C-5. In addition, the X-ray diffraction analysis of mangnardone I is the first example to confirm the structure of bicycloalternarene (BCA) meroterpenoid by single-crystal data. Nine undescribed meroterpenes inhibited nitric oxide (NO) production in LPS-induced RAW 264.7 cells with IC50 values in the range of 4.7–40.0 μ M. Graphical abstract: Nine undescribed shikimate conjugated meroterpenes, as well as eight known compounds, were isolated from solid culture of the fungus Guignardia mangiferae, an endophyte obtained from the leaves of Dendrobium nobile . Nine undescribed meroterpenes exhibited inhibition of nitric oxide (NO) production in LPS-induced RAW 264.7 cells with IC50 values in the range 4.7–40.0 μ M. Image 1 Highlights: Nine undescribed meroterpenes were characterized from fungus G. mangiferae. Compound 1 is meroterpenoid with a hydroxy group at C-5. The absolute configuration of 9 was elucidated by X-ray crystallographic analysis. Nine undescribed meroterpenes exhibited inhibition of nitric oxide (NO).